Chapter 6 - Barley - Kumari, Safaa; Makkouk, Khaled; Najar, Asma (ELSEVIER ACADEMIC PRESS INC, 2023)
Among 30 viruses have been reported on barley, but only few of them are widespread and cause significant economic damage. Among the most important viruses reported to infect barley are BUDVs (such as BYDV-PAV, BYDV-MAV), cereal yellow dwarf virus (CYPV)-RPV, barely yellow striate mosaic virus (BYSMV), and barley stripe mosaic virus (BSMV).